A Strategi Pengembangan Kompetensi Pustakawan di Dinas Perpustakaan dan Kearsipan Kabupaten Gunung Kidul: Strategi Pengembangan Kompetensi Pustakawan di Dinas Perpustakaan dan Kearsipan Kabupaten Gunung Kidul - komahh, nur isti; Masruri, Anis (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
ABSTRACT Introduction. This study aims to determine the strategy of developing the competence of librarians at the Office of the Dinas Perpustakaan dan Kearsipan Kabupaten Gunung Kidul. Data Collection Method. This research uses descriptive qualitative method. Methods of data collection using frank or covert observation, semi-structured interviews, and documentation. The technique of determining the informants used purposive sampling. The data analysis technique in this study uses the theory of Miles and Hubermen, namely data reduction, data presentation, and drawing conclusions. Test the validity of the data in this study using a credibility test which includes: extension of observation, triangulation, and member check. Transferability test, depenability test, and confirmability test. Result and Discussions. The research results are; (1) The librarian competency development strategy is divided into two, namely formal and informal development. Formal development is in the form of: training, technical guidance, workshops, seminars, professional organizations, competitions for outstanding librarians and fostered areas for librarians. Meanwhile, informal librarian competency development includes: being a resource person or speaker, coordinating fellow librarians, networking, and relationships. (2) supporting factors in the implementation of librarian competency development include: motivation within the librarian itself and full support from the service and the Head of the Dinas Perpustakaan dan Kearsipan Kabupaten Gunung Kidul Service. While the inhibiting factors that need special attention are related to the budget for developing the competence of librarians and limiting quotas in an activity. Conclusions. The suggestion to be given for the strategy of developing the competence of librarians at the Office of the Dinas Perpustakaan dan Kearsipan Kabupaten Gunung Kidul is to maximize the available budget for developing the competence of librarians by being more selective in choosing the development activities to be carried out. And for librarians who have the opportunity to take part in training activities, seminars, workshops, technical guidance and other competency development, they can share their knowledge and knowledge with other librarians. Keywords: Strategy, Development, Librarian Competence